Multilayer films comprising ionomers of ethylene acid polymers

By using zinc ionomers or sodium ionomers of vinyl acid copolymers in the multilayer film and adjusting the polymer composition, the problem of difficult balance between stiffness and toughness of the multilayer film is solved, and efficient recycling of the film and excellent mechanical properties are achieved.

CN119836346APending Publication Date: 2025-04-15DOW GLOBAL TECHNOLOGIES LLC +1
View PDF 14 Cites 0 Cited by

Patent Information

Application Number
CN202380035139.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-05-20
Filing Date
2023-05-19
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The existing multilayer films are difficult to achieve a balance between stiffness and toughness, and at the same time, due to the non-recyclable compatibility between materials, it is difficult to perform effective recycling.

Method used

Using a multilayer film of zinc ionomer or sodium ionomer including vinyl acid copolymer, the balance of tear resistance, toughness and stiffness of the film is achieved by adjusting the polymer composition and proportion of the core layer and outer layer, and compatibility with the polyethylene recirculation flow is ensured.

Benefits of technology

The desired balance of multilayer films in terms of tear resistance, toughness and stiffness is achieved, and is fully recyclable compatible, with better performance than or equivalent to other multilayer films.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005092644690000101
    Figure BDA0005092644690000101
  • Figure BDA0005092644690000151
    Figure BDA0005092644690000151
  • Figure BDA0005092644690000161
    Figure BDA0005092644690000161
Patent Text Reader

Abstract

A multilayer film comprising a zinc ionomer or a sodium ionomer of an ethylene acid copolymer is provided. The multilayer film may be fully compatible with a polyethylene recycle stream. The multilayer film includes a first outer layer, a second outer layer, and a core including a first core layer including a zinc ionomer or a sodium ionomer of an ethylene acid copolymer. The multilayer films of the present invention may exhibit improved, maintained, or desirable properties, such as high tear resistance, compared to existing multilayer film structures.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] Embodiments of the present disclosure relate generally to multilayer membranes, and more particularly to multilayer membranes including zinc ionomers or sodium ionomers of ethylene acid copolymers.

[0002] introduction

[0003] The relevant problem that is increasing in the packaging industry is a large amount of packaging waste and the hard packaging with poor balance of rigidity and toughness. The multilayer film incorporating various materials (including polypropylene, polyamide and polyethylene terephthalate) contributes to the bulk packaging in industrial and consumer products. Such films used usually require enough toughness and tear resistance, for example, to avoid the film from breaking during the film wrapping process on the pallet. The combination of layers and materials can allow the good performance of the film, but because different types of materials are not recyclable and compatible with each other, such multilayer films may lack the balance of rigidity and toughness and may be difficult (if not impossible) to recycle together. Along with the demand for relatively small, single material recyclable materials in volume continues to rise, there is still a demand for the multilayer film that can be more easily recycled and show the balance of desired characteristics (such as tear resistance, toughness and / or rigidity). Summary of the invention

[0004] Embodiments of the present disclosure meet one or more of the aforementioned needs by providing a multilayer film that exhibits a desired balance of tear resistance, toughness, and stiffness and includes a recyclable compatible ethylene-based polymer, including a zinc ionomer or a sodium ionomer of an ethylene acid copolymer. The multilayer film can be fully recyclable compatible in a polyethylene recycle stream, and the tear resistance and toughness properties of the multilayer film of the present invention can be comparable to or better than other multilayer films.

[0005] The present invention discloses a multilayer film. In one aspect, the multilayer film comprises a first outer layer, a second outer layer and a core, the core comprising one or more core layers, wherein the first core layer comprises 5 wt % to 45 wt % of a zinc ionomer or sodium ionomer of an ethylene acid copolymer based on the total weight of the first core layer and 55 wt % to 95 wt % of a polyol having a molecular weight of 0.950 g / cm 3 Up to 0.970g / cm 3 and a polyethylene with a density of 0.3 g / 10 min to 10.0 g / 10 min and a melt index (I2) of 0.3 g / 10 min to 10.0 g / 10 min; wherein the first core layer has a thickness of 5% to 40% of the total thickness of the multilayer film.

[0006] Also disclosed herein are articles.An article may include a multilayer film according to embodiments disclosed herein.

[0007] These and other embodiments are described in more detail in the detailed description. DETAILED DESCRIPTION

[0008] Various aspects of the disclosed multilayer film are described in more detail below. The multilayer film can have a variety of applications, including, for example, cast stretch film, blown film, oriented film, stretch hood film, heavy-duty shipping bags, etc. However, the present disclosure should not be construed as limiting the embodiments set forth below, as the present disclosure is an illustrative implementation of the embodiments described herein.

[0009] As used herein, the term "polymer" means a polymeric compound prepared by polymerizing monomers of the same or different types. The generic term polymer thus encompasses the term homopolymer (used to refer to a polymer prepared from only one type of monomer) and the term copolymer. Trace impurities (e.g., catalyst residues) may be incorporated into and / or within the polymer. The polymer may be a single polymer, a polymer blend, or a polymer mixture, including a mixture of polymers formed in situ during polymerization.

[0010] As used herein, the term "copolymer" refers to a polymer formed by the polymerization reaction of at least two monomers having different structures. The term "copolymer" includes terpolymers.

[0011] As used herein, the term "polyethylene" or "ethylene-based polymer" shall mean a polymer comprising a majority amount (>50 wt%) of units derived from ethylene monomers. This includes polyethylene homopolymers and copolymers (meaning units derived from two or more comonomers). Unless otherwise expressly stated, the ethylene copolymers disclosed herein (e.g., zinc ionomers or sodium ionomers of the ethylene acid copolymers described herein) are ethylene-based polymers.

[0012] Common forms of polyethylene known in the art include low density polyethylene (LDPE); linear low density polyethylene (LLDPE); ultra low density polyethylene (ULDPE); very low density polyethylene (VLDPE); single site catalyzed linear low density polyethylene, including linear and substantially linear low density resins (m-LLDPE); ethylene-based plastomers (POPs) and ethylene-based elastomers (POEs); medium density polyethylene (MDPE); and high density polyethylene (HDPE). These polyethylene materials are generally known in the art; however, the following description may help understand the differences between some of these different polyethylene resins.

[0013] The term "LDPE" may also be referred to as "high pressure ethylene polymer" or "highly branched polyethylene" and is defined to mean a polymer that is partially or completely homopolymerized or copolymerized in an autoclave or tubular reactor at pressures above 14,500 psi (100 MPa) using a free radical initiator such as a peroxide (see, e.g., U.S. Pat. No. 4,599,392, which is hereby incorporated by reference). LDPE resins typically have a molecular weight of 0.916 g / cm 3 Up to 0.935g / cm 3 density within the range of .

[0014] The term "LLDPE" includes both resins made using conventional Ziegler-Natta catalyst systems and chromium-based catalyst systems and single-site catalysts (including but not limited to substituted mono- or dicyclopentadienyl catalysts (commonly referred to as metallocenes), constrained geometry catalysts, phosphinimine catalysts, and polyvalent aryloxyether catalysts (commonly referred to as bisphenylphenoxy), and includes linear, substantially linear, or heterogeneous polyethylene copolymers or homopolymers. LLDPE contains less long chain branching than LDPE, and includes substantially linear ethylene polymers as further defined in U.S. Pat. No. 5,272,236, U.S. Pat. No. 5,278,272, U.S. Pat. No. 5,582,923, and U.S. Pat. No. 5,733,155; homogeneously branched linear ethylene polymer compositions, such as those in U.S. Pat. No. 3,645,992; heterogeneously branched ethylene polymers, such as those prepared according to the process disclosed in U.S. Pat. No. 4,076,698; and / or blends thereof (such as U.S. Pat. No. 3,914,342 or U.S. Pat. No. 5,733,155). 5,854,045). LLDPE can be made by gas phase, solution phase or slurry polymerization, or any combination thereof, using any type of reactor or reactor configuration known in the art.

[0015] The term "MDPE" refers to a polyethylene with a density of 0.926 g / cm 3 Up to 0.935g / cm 3 "MDPE" is typically produced using chromium or Ziegler-Natta catalysts or using single-site catalysts, including but not limited to substituted mono- or bis-cyclopentadienyl catalysts (commonly referred to as metallocenes), constrained geometry catalysts, phosphinimine catalysts, and polyvalent aryloxyether catalysts (commonly referred to as bisphenylphenoxy), and typically has a molecular weight distribution ("MWD") greater than 2.5.

[0016] The term "HDPE" refers to a polyethylene having a density greater than about 0.935 g / cm 3 and at most about 0.980 g / cm 3The polyethylene is generally prepared using Ziegler-Natta catalysts, chromium catalysts or single-site catalysts (including but not limited to substituted mono- or bis-cyclopentadienyl catalysts (commonly known as metallocenes), constrained geometry catalysts, phosphinimine catalysts and polyvalent catalysts aryloxyether catalysts (commonly known as bisphenylphenoxy).

[0017] The term "ULDPE" refers to a polyethylene with a density of 0.855 g / cm 3 Up to 0.912g / cm 3 ULDPE is a polyethylene generally prepared with a Ziegler-Natta catalyst, a chromium catalyst or a single-site catalyst (including but not limited to substituted mono- or di-cyclopentadienyl catalysts (commonly referred to as metallocenes), constrained geometry catalysts, phosphinimine catalysts and multivalent catalysts (commonly referred to as bisphenylphenoxy). ULDPE includes but is not limited to polyethylene (based on ethylene) plastomers and polyethylene (based on ethylene) elastomers.

[0018] As used herein, the term "zinc or sodium ionomer of an ethylene acid copolymer" means an ionomer comprising an ethylene acid copolymer having carboxylic acid groups neutralized to a carboxylate salt comprising zinc cations or sodium cations, wherein the ethylene acid copolymer is the polymerization product of greater than 50 weight percent ethylene monomer and greater than 2 weight percent monocarboxylic acid monomer, based on the total weight of monomers present in the ethylene acid copolymer.

[0019] As used herein, the term "core layer" refers to a non-surface layer or non-outer layer of a multilayer film. The core layer is an inner layer of a multilayer film, i.e., a layer positioned between two outer layers. In one embodiment, the first core layer is a non-outer layer of a three-layer film including a first outer layer and a second outer layer. All core layers (i.e., one or more layers) in the multilayer film of the present invention constitute the "core" of the film.

[0020] The terms "comprising," "including," "having," and derivatives thereof are not intended to exclude the presence of any additional components, steps, or procedures, whether or not specifically disclosed. For the avoidance of any doubt, all compositions claimed through use of the term "comprising" may include any additional additives, adjuvants, or compounds, whether polymeric or otherwise, unless stated to the contrary. In contrast, the term "consisting essentially of excludes from the scope of any subsequently recited any other components, steps, or procedures, except those that are not essential to operability. The term "consisting of excludes any ingredient, step, or procedure not specifically recited or listed.

[0021] Multilayer films are disclosed herein. In some embodiments, the multilayer film can be an oriented film oriented in the longitudinal direction and / or the transverse direction. In some embodiments, the multilayer film is a blown film. In other embodiments, the multilayer film is a cast stretch film. In other embodiments, the multilayer film is a stretch hood film.

[0022] The multilayer film according to the embodiments disclosed herein includes a first outer layer, a second outer layer and a core, the core including one or more core layers. The core is positioned between the first outer layer and the second outer layer. The core includes a first core layer, the first core layer including a zinc ionomer or a sodium ionomer of an ethylene acid copolymer and polyethylene.

[0023] The first outer layer and the second outer layer of the multilayer film

[0024] The first outer layer and the second outer layer of the multilayer film are not particularly limited. The first outer layer and the second outer layer may have the same polymer composition or different polymer compositions. In some embodiments, each of the first outer layer and the second outer layer has a thickness of 5% to 35% of the total thickness of the multilayer film.

[0025] In some embodiments, the first outer layer and the second outer layer each include polyethylene. In some embodiments, the first outer layer and / or the second outer layer include ethylene-based polymers such as ULDPE, LLDPE, LDPE, MDPE, or HDPE. For example, in some embodiments, the first outer layer and / or the second outer layer include ULDPE, LLDPE, LDPE, or blends thereof.

[0026] In embodiments where the first outer layer and / or the second outer layer comprises polyethylene, the polyethylene may have a molecular weight less than or equal to 0.940 g / cm 3 Density of less than or equal to 0.940 g / cm 3 All individual values ​​and subranges of; for example, the density of polyethylene can be from the lower limit 0.870g / cm 3 、0.880g / cm 3 、0.890g / cm 3 、0.910g / cm 3 , 0.920g / cm 3 Up to 0.940g / cm 3 , 0.935g / cm 3 、0.930g / cm 3 or 0.925g / cm 3 . This article includes and discloses 0.870 g / cm 3 and 0.940g / cm 3 All individual values ​​and subranges in between.

[0027] In the embodiment where the first outer layer and / or the second outer layer include polyethylene, the polyethylene may have a melt index (I2) in the range of 0.1 g / 10 min to 50 g / 10 min. All individual values ​​and subranges of 0.1 g / 10 min to 50 g / 10 min are disclosed herein and included. For example, the polyethylene may have a melt index (I2) in the range of 0.1 g / 10 min to 40 g / 10 min, 0.1 g / 10 min to 30 g / 10 min, 0.1 g / 10 min to 20 g / 10 min, 0.1 g / 10 min to 10 g / 10 min, or 0.1 g / 10 min to 5 g / 10 min.

[0028] Commercially available examples of polyethylene that can be used for the first outer layer and / or the second outer layer include polyethylene available from The Dow Chemical Company under the name ATTANE TM Those commercially available include, for example, ATTANE TM 4404G, and the name INNATE TM Those commercially available include, for example, INNATE TM ST 50.

[0029] In some embodiments, the first outer layer and the second outer layer comprise ULDPE. In embodiments where the first outer layer and / or the second outer layer comprise ULDPE, the ULDPE may have a molecular weight less than or equal to 0.912 g / cm 3 Density. This article includes and discloses less than or equal to 0.912 g / cm 3 All individual values ​​and subranges of; for example, the density of ULDPE may be 0.855 g / cm 3 、0.860g / cm 3 、0.870g / cm 3 、0.880g / cm 3 、0.890g / cm 3 The lower limit is 0.912g / cm 3 、0.910g / cm 3 , 0.908g / cm 3 or 0.906 g / cm 3 The upper limit of 0.855 g / cm is included and disclosed herein. 3 and 0.912g / cm 3 All individual values ​​and subranges in between.

[0030] In embodiments where the first outer layer and / or the second outer layer comprises ULDPE, the ULDPE may have a melt index (I2) in the range of 0.1 g / 10 min to 50 g / 10 min. All individual values ​​and subranges of 0.1 g / 10 min to 50 g / 10 min are disclosed and included herein. For example, the ULDPE may have a melt index (I2) in the range of 0.1 g / 10 min to 40 g / 10 min, 0.1 g / 10 min to 30 g / 10 min, 0.1 g / 10 min to 20 g / 10 min, 0.1 g / 10 min to 10 g / 10 min, or 0.1 g / 10 min to 5 g / 10 min.

[0031] Multilayer core

[0032] The multilayer film includes a core. The core includes one or more core layers. In some embodiments, the core includes 100% by weight of an ethylene-based polymer based on the total weight of the core, including zinc ionomers or sodium ionomers of ethylene acid copolymers (described below). The core is positioned between the first outer layer and the second outer layer. The core includes the first core layer. In some embodiments, the multilayer film disclosed herein is a three-layer film including the first outer layer, the second outer layer and the core, and the core includes the first core layer. In other embodiments, the multilayer film includes at least five layers. For example, in some embodiments, the core includes the first core layer, the second core layer and the third core layer, wherein the first core layer is positioned between the first outer layer and the third core layer, the second core layer is positioned between the third core layer and the second outer layer, and the third core layer is positioned between the first core layer and the second core layer (i.e., the first outer layer / first core layer / third core layer / second core layer / second outer layer). In the embodiment where the core includes the first core layer, the second core layer and the third core layer, the multilayer film includes at least five layers.

[0033] The core includes a first core layer. The first core layer includes 5 wt % to 45 wt % of zinc ionomer or sodium ionomer of ethylene acid copolymer based on the total weight of the first core layer and 55 wt % to 95 wt % of a 0.950 g / cm 3 Up to 0.970g / cm 3 The first core layer has a thickness of 5% to 40% of the total thickness of the multilayer film.

[0034] The first core layer comprises zinc ionomer or the sodium ionomer of the ethylene acid copolymer of 5 wt % to 45 wt % based on the gross weight of the first core layer.All individual values ​​and subranges of 5 wt % to 45 wt % are disclosed herein and are included.For example, the first core layer may comprise zinc ionomer or the sodium ionomer of the ethylene acid copolymer of 5 wt %, 10 wt %, 15 wt %, 20 wt % or 22 wt % to an upper limit of 27 wt %, 30 wt %, 35 wt %, 40 wt % or 45 wt % based on the gross weight of the first core layer.

[0035] In some embodiments, the first core layer comprises a zinc ionomer of an ethylene acid copolymer. In other embodiments, the first core layer comprises a sodium ionomer of an ethylene acid copolymer. In some embodiments, the zinc ionomer or sodium ionomer of an ethylene acid copolymer has a molecular weight of 0.940 g / cm 3 Up to 0.960g / cm 3 or 0.945g / cm 3 Up to 0.955g / cm 3 In some embodiments, the zinc ionomer or sodium ionomer of the ethylene acid copolymer has a melt index (I2) of less than 3.0 g / 10 min, or less than 2.0 g / 10 min, or less than 1.0 g / 10 min.

[0036] Commercially available examples of sodium ionomers of ethylene acid copolymers that can be used in the first core layer and / or the second core layer include SURLYN TM 1707. Commercially available examples of zinc ionomers of ethylene acid copolymers that can be used in the first core layer and / or the second core layer include SURLYN TM 1706.

[0037] The first core layer includes 55 wt % to 95 wt % of a 0.950 g / cm 3 Up to 0.970g / cm 3 The polyethylene of density and melt index (I2) of 0.3g / 10min to 10.0g / 10min. All individual values ​​of 55 wt % to 95 wt % are disclosed herein and included. For example, the first core layer may include polyethylene from a lower limit of 60 wt %, 65 wt %, 70 wt %, 72 wt % or 73 wt % to an upper limit of 78 wt %, 80 wt %, 85 wt %, 90 wt % or 95 wt % based on the gross weight of the first core layer.

[0038] The polyethylene of the first core layer has a g / cm 3 Up to 0.970g / cm 3In one or more embodiments, the polyethylene of the first core layer is HDPE (high density polyethylene). All individual values ​​and subranges are disclosed and included herein. For example, the polyethylene of the first core layer may have a lower limit of 0.950 g / cm 3 , 0.952g / cm 3 , 0.954g / cm 3 、0.956g / cm 3 , 0.958g / cm 3 or 0.960g / cm 3 and the upper limit is 0.970g / cm 3 、0.968g / cm 3 , 0.966g / cm 3 , 0.965g / cm 3 or 0.964 g / cm 3 The polyethylene of the first core layer has a melt index (I2) of 0.3 g / 10 min to 10.0 g / 10 min. All individual values ​​and subranges are disclosed and included herein. For example, the polyethylene of the first core layer may have a melt index (I2) with a lower limit of 0.3 g / 10 min, 0.4 g / 10 min, 0.5 g / 10 min, 0.6 g / 10 min, 1.0 g / 10 min, 2.0 g / 10 min, 3.0 g / 10 min, 4.0 g / 10 min, 5.0 g / 10 min, 6.0 g / 10 min or 7.0 g / 10 min and an upper limit of 10.0 g / 10 min, 9.0 g / 10 min, 8.5 g / 10 min, 7.0 g / 10 min, 6.0 g / 10 min, 5.0 g / 10 min, 4.0 g / 10 min, 3.0 g / 10 min, 2.0 g / 10 min or 1.0 g / 10 min.

[0039] Commercially available examples of polyethylene that can be used for the first core layer and / or the second core layer include polyethylene available from The Dow Chemical Company under the name ELITE TM 5960G1 and DOW TM DMDA-8007NT 7 is commercially available.

[0040] In some embodiments, the first core layer has a Raman measured % crystallinity of 50% to 63%. Raman crystallinity can be measured according to the test method described below.

[0041] In some embodiments, the multilayer film includes a second core layer. In some embodiments, the second core layer has the same polymer composition as the first core layer. In other embodiments, the second core layer has a different polymer composition than the first core layer. In some embodiments, the second core layer includes 5 wt % to 45 wt % of a zinc ionomer or sodium ionomer of an ethylene acid copolymer and 55 wt % to 95 wt % of a polyvinyl alcohol having a molecular weight of 0.950 g / cm 3 Up to 0.970g / cm 3 The polyethylene and zinc ionomer or sodium ionomer of the second core layer of ethylene acid copolymer may have the same density and melt index (I2) parameters as the polyethylene and ionomer of the first core layer.

[0042] In some embodiments, the multilayer film includes a third core layer. In such embodiments, the third core layer is positioned between the first core layer and the second core layer and includes a melt index of less than 7.0 g / 10 min and a viscosity of less than 0.940 g / cm 3 The polyethylene of the third core layer may have a melt index of less than 7.0 g / 10 min, or less than 6.0 g / 10 min, or less than 5.0 g / 10 min. The polyethylene of the third core layer may have a melt index of less than 0.940 g / cm 3 , or less than 0.930g / cm 3 , or less than 0.925g / cm 3 density.

[0043] additive

[0044] It should be understood that any of the aforementioned layers may further include one or more additives known to those skilled in the art, such as antioxidants, UV stabilizers, heat stabilizers, slip agents, antiblocking agents, antistatic agents, pigments or colorants, processing aids, crosslinking catalysts, flame retardants, fillers, and foaming agents. For example, in some embodiments, the first outer layer and the second outer layer each include an antiblocking agent.

[0045] Multilayer film

[0046] The multilayer films disclosed herein can be produced using techniques known to those skilled in the art based on the teachings herein. For example, the multilayer films can be produced by coextrusion. The formation of coextruded multilayer films is known in the art and is applicable to the present disclosure. The coextrusion system for making the multilayer film uses at least two extruders to feed a common die assembly. The number of extruders depends on the number of different materials or polymers that make up the coextruded film. For example, a five-layer coextrusion may require up to five extruders, but if two or more layers are made of the same material or polymer, fewer extruders may be used.

[0047] In various embodiments, the multilayer films of the present invention can have several desirable properties. Without being bound by any theory, the specific structure of the multilayer film, together with the specific polyethylene and zinc ionomer or sodium ionomer of ethylene acid copolymer included in the core, can produce a specific layer morphology in the multilayer film that promotes higher energy absorption when the structure is mechanically required, thereby resulting in the multilayer film having desirable tear resistance, toughness and / or stiffness properties.

[0048] In some embodiments, the multilayer film has a thickness between 6 microns and 150 microns, or alternatively between 6 microns and 100 microns, or alternatively between 6 microns and 50 microns.

[0049] In some embodiments, based on the total weight of the multilayer film, the multilayer film of the present invention comprises at least 90% by weight of ethylene-based polymers, or at least 95% by weight of ethylene-based polymers, or at least 99% by weight of ethylene-based polymers, or at least 99.5% by weight of ethylene-based polymers, or at least 99.9% by weight of ethylene-based polymers. Because in some embodiments, the multilayer film comprises at least 90% by weight of ethylene-based polymers, they can be compatible with polyethylene recycling streams. In some embodiments, the multilayer film is substantially composed of 100% by weight of ethylene-based polymers based on the total weight of the multilayer film.

[0050] In some embodiments, the multilayer film is a longitudinally oriented film. In other embodiments, the multilayer film is a cast stretch film. In other embodiments, the multilayer film is a blown film.

[0051] Cast Stretch Film and Blown Film

[0052] In one embodiment, the multilayer film of the present invention is a cast stretch film. Cast stretch film is a high transparency film for protecting and utilizing manufactured products or articles for transportation and storage. It is highly desirable that the cast stretch film has a high transverse tear strength to minimize catastrophic damage during pallet packaging. The difference between cast stretch film and blown stretch film is the manufacturing method. The main differences between cast film and blown film involve cooling methods, film orientation, line speed and thickness control. Compared with blown film, cast film generally exhibits better optical properties and a much higher degree of longitudinal orientation. Cast stretch film can be produced based on the teachings of this article using techniques known to those skilled in the art.

[0053] In embodiments where the multilayer film is a cast stretch film, the cast stretch film may have an ESTL tear of greater than 0.4 s / micrometer. The ESTL tear may be measured according to the test method described below. The ESTL tear measurement of the propagation time in seconds (s) may be divided by the thickness of the film in micrometers to provide a s / micrometer measurement.

[0054] In one embodiment, the multilayer film of the present invention is a blown film. The blown film can be prepared by methods known in the art. In embodiments where the multilayer film is a blown film, the blown film can have at least one of the following properties: a longitudinal Elmendorf tear strength greater than 0.13 N / micrometer and / or a dart impact B greater than 0.031 N / micrometer. The longitudinal Elmendorf tear strength and dart impact B can be measured according to the following test methods.

[0055] Products

[0056] Embodiments of the present invention also provide articles comprising any of the multilayer films of the present invention described herein. Examples of such articles may include wrappers, packages, flexible packages, bags, and pouches. In view of the teachings herein, the articles of the present invention may be formed from the multilayer films disclosed herein using techniques known to those skilled in the art.

[0057] Test Method

[0058] density

[0059] Density is measured according to ASTM D792 and is expressed in grams / cm 3 (g / cm 3 )express.

[0060] Melt index (I2)

[0061] Melt index (I2) is measured according to ASTM D-1238 at 190° C. and 2.16 kg. The values ​​of melt index are reported in g / 10 min, which corresponds to the grams eluted per 10 minutes.

[0062] Raman microscopy

[0063] Raman microscopy and multivariate calibration are used to measure the % crystallinity of individual layers of multilayer films. Raman microscopy, as a type of vibrational spectroscopy technique, is sensitive to the vibrations of the polymer backbone and can provide information about both the amorphous and crystalline phases of polymer and polyethylene compositions. Raman can use visible or near infrared radiation and provides a lateral spatial resolution of about 0.8 microns to 1.2 microns when coupled to an optical microscope (depending on the excitation laser and microscope objective used).

[0064] A partial least squares (PLS) model was constructed to relate the Raman data to the percent crystallinity (%) calculated from the annealed polyethylene density. The model was then used to predict the percent crystallinity (%) of each layer in the multilayer film. The annealed density was measured according to ASTM D792. The percent crystallinity (%) was calculated from the measured annealed density using the following equation (Equation 1):

[0065]

[0066] Where: a = 0.855 g / cc (100% amorphous) and ρ c = 1.000 g / cc (100% crystalline) density.

[0067] Polarized Raman spectra were collected using an equivalent Thermo Scientific DXR2 micro-Raman instrument. Raman spectra were collected using a 900 grooves / mm grating. The spectral range covered 50 cm -1 Up to 3500cm -1 The Raman shift is 0.964 cm. -1 Other data acquisition parameters are as follows. Acquisition time: 3-10 seconds; Number of acquisitions: 3 to 6; Dark current subtraction, cosmic ray filter, and white light correction: On. Calibration data were recorded with an Olympus M PlanN 100x (0.90NA) objective using a 50 micron pinhole.

[0068] The density range of the twenty-eight samples is 0.859 g / cm 3 Up to 0.964g / cm 3 The polyethylene composition resins were used for calibration and cross-validation of the PLS model. The PLS model was also validated using an independent set of density patches and then used to measure the resin crystallinity of the resins used for the individual layers of the multilayer film. The PLS model was generated using TQ Analyst TM Software, built with the following parameters: Spectral region: 1571 cm 1 Up to 971cm -1 ; Normalized: integrated area 1356cm -1 Up to 1227cm -1 -Same baseline points; Total number of samples: 28; Number of calibration standards: 26; Number of independent cross-validation samples: 2; Number of independent validation samples: 6; Data pre-processing for: Annealed base resin density model and calculated crystallinity % model - average centering, 2nd derivative, SG smoothing (15 points, 3rd order polynomial); Number of factors used for calibration of both models: Annealed base resin density and calculated crystallinity % = 4.

[0069] After validating the PLS model, cross sections of the multilayer films were prepared via cryosectioning. Depolarized Raman spectra were collected in five different locations within each layer using a 100x (0.9NA) objective and a 25 micron pinhole. The resulting Raman spectra from each layer were averaged, and the averaged spectra were used to measure the layer crystallinity % using the PLS model.

[0070] Ultimate stretch

[0071] The ultimate stretch value is measured using a Highlight Stretch Film Test Station (Highlight Industries, Wyoming, Michigan, USA). The film roll is placed on the Highlight's unwinding roller and wound through the equipment rollers as instructed by the Highlight test procedure. Select the Ultimate Stretch Value test from the test menu, and select the method (Standard, Heavy, Light). The default is Standard and should be used for most films. Films thicker than 1 mil (25.4 μm) are heavy, while the light method should be used for films below 50 gauge (~12 μm) or films less than 15 inches wide. The selected method changes the slope of the test. Once the method is selected, the test is started and the film is stretched between two pre-stretch rollers. Stretching is achieved by the speed difference between the pre-stretch rollers. The film is stretched until a uniform break is observed between the two pre-stretch rollers. If the film break is not in a straight line, or if the film breaks somewhere other than in the middle of the pre-stretch rollers, the break is considered a major break and is not included in the data. However, the data reported on the graph represents the failure point; the tensile force data point is selected when the stretch passes 200% stretch. The test was repeated at least 3 times, and the average US and SF were reported.

[0072] Pallet Piercing-Type A Load (OPP-A)

[0073] This test uses the Bruceton step method to determine the maximum load force that the film can be wrapped three times without failure by the test probe. The test probe is inserted into the test bench at the desired protrusion distance. The protrusion distance is determined by the thickness of the film. Thicker films are usually tested with a protrusion of 12 inches, while thinner films are tested at 5 inches. The film is positioned so that the test probe is aligned with the center of the film. The film is attached to the test bench and the wrapper is started. Once the wrapper reaches 250% pre-stretching, the film is allowed to pass through up to three wraps on the probe. Start with a low F2 force of 7lbs. and wrap the film three times. If the film is not pierced by the probe, the test is repeated with an increased F2 force in increments of 0.5lbs. until it breaks. At each 0.5lb. increment, the film is manually pushed onto the probe and a new set of films is tested. Any breakage of the film during any packaging is considered to be a failure under the force to load setting. According to the performance of the film under the load setting (i.e., pass or fail), the force of the load is adjusted up or down, and the test is repeated under the new load setting. This continues until the maximum force of rupture is not found. The ruptured F2 force represents the pallet puncture value of the film, and standard deviations are not usually reported unless the test is repeated more than 2 times starting from 7 lbs. The highest pass F2 force is reported, where data significance is considered to be + / -1 lb. It should be understood that the A-type load test is commonly used in pallet packaging, and those of ordinary skill in the art will recognize its meaning as used herein. Table 8 provides the equipment and settings used in this method.

[0074] equipment Lantech SHC Film Test Wrapper Pre-stretching 250% Turntable speed 9rpm Load force (F2) Variable Probe Type 4" x 4" blunt rod Probe protrusion distance 12n

[0075] Pallet Piercing-Type B (OPP-B)

[0076] If the combined pallet is not uniform in shape and has limited irregularities, it is defined as "Type B load". This test uses the Bruceton step method to determine the maximum load force at which the film can be wrapped three times without failure by overlapping the test probe. The test probe is inserted into the test bench at the desired protrusion distance. All films are tested by a 2-inch × 2-inch blunt metal probe extending 6 inches. The film is positioned so that the test probe is aligned with the center of the film. The film is attached to the test bench and the wrapper is started. Once the wrapper reaches 250% pre-stretching, the film is allowed to pass through a maximum of three wraps on the probe. Starting with a stretched film tension / load force (F2) of 7 lbs., the film is wrapped three times. If the film is not pierced by the probe, the test is repeated with an increased F2 force in increments of 0.5 lbs. until it breaks. Any breakage of the film during any packaging is considered to be a failure under the force to load setting. Once the F2 force reaches the point where failure begins to occur, the test is repeated 6 times at one force setting. If the film passes 4 of the 6 tests, the film F2 force increases. If the film fails in 4 of 6 tests, the test is stopped, and this is considered to be the failure point of the film. According to the performance of the film under the load setting (i.e., pass or fail), the force of the load is increased / reduced and the test is repeated under the new load setting. This continues until the maximum force of rupture is not observed. The highest F2 force passed is reported as the pallet puncture (OPP) value. It is observed that the standard variation of this test is + / -1lb.. It should be understood that the B-type load test is commonly used for pallet packaging, and those of ordinary skill in the art will recognize its meaning as used herein. Table 9 below provides the equipment and settings used in this method.

[0077] equipment Lantech SHC Film Test Wrapper Pre-stretching 250% Turntable speed 9rpm Load force (F2) Variable Probe Type 2" x 2" blunt rod Probe protrusion distance 6in

[0078] Torn on pallet

[0079] This test uses the Bruceton step method to determine the maximum load force that a film can pass over a test probe fixed with a blade to initiate puncture. The test probe is inserted into the test station with the desired protrusion distance. The film is positioned so that the test probe is aligned with the center of the film. The film is attached to the test station and the wrapper is started. Once the wrapper reaches 250% pre-stretch, the film is allowed to pass the probe. For this test, a single layer of film is tested. The film tension (F2 force) is increased in increments of 0.5 lbs. from an initial low value of approximately 7 lbs. until the film is completely torn in the cross direction (CD) or transverse direction (TD). The pallet tear value is recorded as the highest F2 force that causes the initial puncture to fail without propagating through the entire width of the film. Table 10 provides the equipment and settings used in this method

[0080] equipment Lantech SHC Film Test Wrapper Pre-stretching 250% Turntable speed 9rpm Load force (F2) Variable Probe Type 4" x 4" blunt bar with razor blade attached Probe protrusion distance 5in

[0081] ESTL tear

[0082] ESTL tear is measured using an ESTL Film Property Tester (ESTL, Deerlijk, Belgium) - FPT-750 Film Property Tester. Select "Tear Propagation" from the test menu and then select the W packaging method. The following table provides the parameters selected on the equipment to measure the rupture time (ESTL tear). The sample film is placed in a pre-stretched and tensioned state, and then the film is clamped. A small "spear-shaped knife" is used to make a small vertical cut in the film. Once this cut is made, the canvas releases the film. After one second, the reel begins to pull the film at a constant speed. The other shafts are blocked. This creates a tensile force in the film after the initial cut. The FPT-750 Film Property Tester monitors how long it takes and how much force it takes to destroy the entire film height. The test is repeated 3 times and the average rupture time is reported in seconds (s).

[0083] Strain begins % 250.0 Line speed ft / min 195 Piercing probe increase Unwinding tension Pound force 6.70 Curl strain % 10.0 Load stretch % 285.0

[0084] ASTM D882-2% Secant Modulus CD and MD

[0085] 2% Secant Modulus is measured in the cross direction (CD) and in the machine direction (MD) according to ASTM D882. This test involves the determination of the tensile or extension properties of plastics in the form of thin sheets (including films) with a thickness of less than 1 mm (0.04 in). Films are arbitrarily defined as having a nominal thickness of no more than 0.25 mm (0.010 in). The tensile properties may vary with specimen preparation, separation speed and test environment. Therefore, for the most accurate comparison of two or more materials, all specimens should be prepared and tested in exactly the same way. The elastic modulus measurement is a special case of this test, in which the modulus is calculated by dividing the tensile stress by the corresponding strain of the linear portion of the curve or the extended portion of the linear line after compensation has been applied. If there is no linear behavior, a tangent is drawn at the inflection point to provide end compensation by using the intersection of the tangent with the strain axis as zero strain. The secant modulus can then be calculated as the ratio of the stress to the corrected strain at any point on the curve. The values ​​of the secant modulus are reported at 1,2% strain in both the machine direction (MD) and the cross direction (CD).

[0086] ASTM D1709-Dart Impact

[0087] Dart Drop Impact B is measured according to ASTM D1709. The Film Dart Drop Test determines the energy that causes a plastic film to fail under specified impact conditions when subjected to a free-falling dart. The test result is the energy expressed in terms of the weight of a projectile dropped from a specified height that will cause 50% of the specimens tested to fail.

[0088] After the film was produced, the film was conditioned at 23°C (+ / -2°C) and 50% RH (+ / -5) for at least 40 hours according to ASTM standards. According to ASTM standards, standard test conditions are 23°C (+ / -2°C) and 50% RH (+ / -5).

[0089] Test results can be reported by Method A using a 1.5" diameter dart head and a 26" drop height, or Method B using a 2.0 diameter dart head and a 60" drop height. The sample thickness is measured at the center of the sample, and the sample is then clamped by a 5" inside diameter annular specimen holder. The dart is loaded over the center of the sample and released by a pneumatic or electromagnetic mechanism.

[0090] The test is performed according to the "ladder" method. If a sample fails, a new sample is tested with the weight of the dart reduced by a known and fixed amount. If the sample does not fail, a new sample is tested with the weight of the dart increased by a known amount. After 20 specimens have been tested, the number of failures is determined. If this number is 10, the test is complete. If the number is less than 10, the test continues until 10 failures are recorded. If the number is greater than 10, the test is continued until the sum of non-failures is 10. The dart drop strength is determined from these data according to ASTM D1709 and expressed in grams as Type A dart drop impact. All samples analyzed were 2 mils thick.

[0091] Breaking puncture energy

[0092] This test is based on the ASTM D5748 method for protrusion puncture resistance of stretch wrap films. The film specimen is held in a pneumatic grip with a 4" diameter opening while a probe moving at a slow speed (10in / m) attempts to puncture the specimen. This method imparts biaxial stress, which represents the type of stress encountered in many end-use applications of packaging films. Two probes can be used for testing. The Dow method probe is stainless steel with a round 1 / 2" diameter head, while the ASTM probe is Teflon-coated stainless steel with a teardrop shape and a 0.75" diameter shape as specified in ASTM D5748.

[0093] ASTM D1922-Elmendorf Tear CD and MD

[0094] The test follows ASTM D1922, where a modified Pro-Tear Electronic Elmendorf Tear tester is used to measure the force (in grams) required to propagate a tear in a film specimen. Acting through gravity, the pendulum swings in an arc, tearing the specimen from the pre-cut slit. The tear propagates in the cross direction. The test can be measured in both the machine direction (MD) and the cross direction (CD).

[0095] Example

[0096] Table 1 below lists the materials included in the exemplary multilayer films discussed below. With the exception of Braskem DS6D82, all of the materials listed below are ethylene-based polymers and are commercially available from The Dow Chemical Company, Midland, Michigan.

[0097] Table 1 – Materials List

[0098]

[0099]

[0100] *This value for Braskem DS6D82 is the melt flow of polypropylene measured according to ASMT D-1238 at 230°C / 2.16kg.

[0101] Cast Film Example

[0102] Two sets of multilayer films were formed on a Dr Collin coextrusion cast film line. For the first set, the Dr Collin coextrusion film line had the following parameters – target film thickness: 15 μm; extrudate: 5 extruders; layer configuration: A / B / C / D / E; layer distribution (%): 10 / 20 / 20 / 20 / 30; throughput – 550 kg / h; chill roll temperature – 21°C; die temperature – 280°C; air gap = 5 mm; melt temperatures of extruders A, B, C, D and E were 252°C, 197°C, 280°C, 280°C and 280°C, respectively.

[0103] For the second set, the Dr Collin coextrusion film line had the following parameters – target film thickness: 15 μm; extrudate: 5 extruders; layer configuration: A / B / C / D / E; layer distribution (%): 10 / 15 / 30 / 15 / 30; throughput – 550 kg / h; chill roll temperature – 21°C; die temperature – 280°C; air gap = 5 mm; melt temperatures of extruders A, B, C, D and E were 255°C, 200°C, 280°C, 280°C and 280°C respectively.

[0104] For the first group, five-layer cast stretch films having a thickness of 15 microns were formed and designated as Inventive (Inv.) Examples and Comparative (Comp.) Examples. Each of the Example films had a structure of A / B / C / D / E, where A was the first outer layer, B was the first core layer, C was the third core layer, D was the second core layer, and E was the second outer layer. Table 2 reports the structure of the five-layer multilayer films formed. For each of these Examples, the first outer layer had a thickness of 10% of the total thickness of the film; the first core layer had a thickness of 20% of the thickness of the film; the third core layer had a thickness of 20% of the thickness of the film; the second core layer had a thickness of 20% of the thickness of the film; and the second outer layer had a thickness of 30% of the thickness of the film.

[0105] Table 2 – Five-layer multilayer: The first group of membrane structures

[0106]

[0107] For the second group, five-layer cast stretch films having a thickness of 15 microns were formed and designated as Inventive (Inv.) Examples and Comparative (Comp.) Examples. Each of the Example films had a structure of A / B / C / D / E, where A was the first outer layer, B was the first core layer, C was the third core layer, D was the second core layer, and E was the second outer layer. Table 3 reports the structure of the five-layer multilayer films formed. For each of these Examples, the first outer layer had a thickness of 10% of the total thickness of the film; the first core layer had a thickness of 15% of the thickness of the film; the third core layer had a thickness of 30% of the thickness of the film; the second core layer had a thickness of 15% of the thickness of the film; and the second outer layer had a thickness of 30% of the thickness of the film.

[0108] Table 3 – Five-layer multilayer: Second group of membrane structures

[0109]

[0110] The thickness, ultimate tensile, ESTL tear (propagation time), pallet tear, pallet puncture-type A load (OPP-A) and pallet puncture-type B load (OPP-B) of each of the comparative examples and the inventive examples were measured. Table 4 below provides the results of the first group of example films. Table 5 below provides the results of the second group of example films. As can be seen from Table 4 below, Example 1 of the present invention, which includes 100% by weight of an ethylene-based polymer and is compatible with a polyethylene recycling stream, has significantly better ESTL tear and pallet tear than Comparative Example 1, Comparative Example 3 and Comparative Example 4. Although Comparative Example 2 has better ESTL tear and pallet tear, it includes a mixture of polypropylene and polyethylene. Example 1 of the present invention has the desired ultimate tensile and pallet puncture. As can be seen from Table 5 below, Example 2 of the present invention, which includes 100% by weight of an ethylene-based polymer and is compatible with a polyethylene recycling stream, has better ESTL tear than Comparative Example 5, Comparative Example 7 and Comparative Example 8. Comparative Example 6 has a higher ESTL tear than Example 2 of the present invention, and it includes a mixture of polypropylene and polyethylene. Inventive Example 2 has desirable ultimate tensile and pallet penetration.

[0111] Table 4 - Properties of Five Layers: First Set of Cast Stretch Film Examples

[0112] Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Embodiment 1 of the present invention Thickness(μm) 15 15 15 15 15 Ultimate tensile strength (%) 330 363 370 350 363 ESTL tear (seconds) 5.54 16.60 6.7 2.44 10.53 Pallet tear (lbs) 9.33 14.5 11.67 9.5 12.17 OPP-B 13 13.8 14 12.8 12 OPP-A 9 12 11.3 13.3 9.5

[0113] Table 5 - Properties of Five Layers: Second Set of Cast Stretch Film Examples

[0114] Comparative Example 5 Comparative Example 6 Comparative Example 7 Comparative Example 8 Embodiment 2 of the present invention Thickness(μm) 15 15 15 15 15 Ultimate tensile strength (%) 330 390 363 343 383 ESTL tear (seconds) 5.54 24.3 21.4 1.51 24.5 Pallet tear (lbs) 9.33 21.80 12.30 8.17 12.00 OPP-B 13.0 13.0 12.5 11.8 11.8 OPP-A 9.0 14.5 14.7 15.3 15.3

[0115] Blown Film Example

[0116] The multilayer film was formed on a Dr Collin blown film line with 5 extruders. The Dr Collin blown film line had the following parameters: layer distribution (%): 33 / 12 / 10 / 12 / 33 (for comparative example 14) and 30 / 15 / 10 / 15 / 30 (for the remaining examples); lead-out: 4.5 m / min; blow-up ratio – BUR: 2.5; die gap: 1.8 mm; die temperature – 235°C; the melt temperatures of extruders A, B, C, D, E were 235°C, 240°C, 234°C, 240°C, and 235°C, respectively.

[0117] Five-layer blown films were formed and designated as Inventive (Inv.) Examples and Comparative (Comp.) Examples. Each of the Example blown films had a structure of A / B / C / D / E, wherein A was the first outer layer, B was the first core layer, C was the third core layer, D was the second core layer, and E was the second outer layer. Table 6 reports the structure of the multilayer films formed. For each of these Examples (except Comparative Example 14), the first outer layer had a thickness of 30% of the total thickness of the film; the first core layer had a thickness of 15% of the thickness of the film; the third core layer had a thickness of 10% of the thickness of the film; the second core layer had a thickness of 15% of the thickness of the film; and the second outer layer had a thickness of 30% of the thickness of the film. Comparative Example 14 is a technical three-layer blown film in which the core comprises the same polymer composition and the first outer layer has a thickness of 33% of the total thickness of the film; the first core layer has a thickness of 34% of the thickness of the film; and the second outer layer has a thickness of 33% of the thickness of the film.

[0118] Table 6 – Blown film structure

[0119]

[0120]

[0121] The blown film comparative examples and inventive examples were each measured for cross direction (CD) 2% secant modulus, machine direction (MD) 2% secant modulus, dart impact type B, break puncture energy, CD Elmendorf tear, and MD Elmendorf tear. The results are provided in Tables 7 and 8 below. As can be seen from Table 7, the inventive examples have significantly better break puncture energy and Elmendorf tear in CD and MD than the comparative examples. The inventive examples also have a balance of other desirable properties.

[0122] Table 7 - Comparative properties of blown film examples

[0123]

[0124] Raman microscopy was used to measure the % crystallinity of the first core layer of certain exemplary blown multilayer films. Table 8 reports the results.

[0125] Table 8 - Raman Microscopy Crystallinity % of First Core Layer

[0126]

Claims

1. A multilayer film comprising: The first outer layer, the second outer layer and the core, the core comprising one or more core layers, wherein the first core layer comprises 5 wt % to 45 wt % of zinc ionomer or sodium ionomer of ethylene acid copolymer based on the total weight of the first core layer and 55 wt % to 95 wt % of a 0.950 g / cm 3 Up to 0.970g / cm 3 and a polyethylene with a density of 0.3 g / 10 min to 10.0 g / 10 min and a melt index (I2) of 0.3 g / 10 min to 10.0 g / 10 min; wherein the first core layer has a thickness of 5% to 40% of the total thickness of the multilayer film.

2. The multilayer film of claim 1, wherein the first outer layer and the second outer layer each comprise polyethylene.

3. The multilayer film of any preceding claim, wherein the multilayer film comprises greater than 80 weight percent of the ethylene-based polymer, based on the total weight of the multilayer film.

4. The multilayer film of any preceding claim, wherein the core comprises 100 wt% of the ethylene-based polymer, based on the total weight of the core.

5. The multilayer film of any preceding claim, wherein the first core layer has a Raman measured % crystallinity of 50% to 63%.

6. The multilayer film of any preceding claim, wherein the second core layer comprises 5 to 45 wt% of a zinc ionomer or sodium ionomer of an ethylene acid copolymer and 55 to 95 wt% of a polyol having a molecular weight of 0.950 g / cm 3 Up to 0.970g / cm 3 Density polyethylene.

7. The multilayer film of claim 6, wherein the third core layer comprises a melt index of less than 7.0 g / 10 min and a 3 A polyethylene having a density of , and wherein the third core layer is positioned between the first core layer and the second core layer.

8. The multilayer film of any preceding claim, wherein the multilayer film is a cast stretch film having an ESTL tear greater than 0.4 s / micrometer.

9. The multilayer film according to claims 1 to 6, wherein the multilayer film is a blown film having at least one of the following properties: a longitudinal Elmendorf tear strength greater than 0.13 N / micrometer and / or a dart impact B greater than 0.031 N / micrometer.

10. An article comprising the multilayer film according to any preceding claim.

Citation Information

Patent Citations

  • Process for preparation of homogenous random partly crystalline copolymers of ethylene with other alpha-olefins

    US3645992A

  • Ethylene polymer blend and polymerization process for preparation thereof

    US3914342A

  • Hydrocarbon interpolymer compositions

    US4076698A

  • Interpolymers of ethylene and unsaturated carboxylic acids

    US4599392A

  • Elastic substantially linear olefin polymers

    US5272236A